Zinc oxide/graphene nanocomposite as efficient photoelectrode in dye‐sensitized solar cells: Recent advances and future outlook. (2nd February 2022) - Mahalingam, Savisha; Low, Foo Wah; Omar, Azimah; Manap, Abreeza; Rahim, Nasrudin Abd; Tan, Chun Hui; Abdullah, Huda; Voon, Chun Hong; Rokhmat, Mamat; Wibowo, Edy; Oon, Cheen Sean
Summary: Dye‐Sensitized Solar Cells (DSSCs), also known as Grätzel cells, are a third‐generation photovoltaic technology that has garnered extensive interest due to its simplicity of fabrication, economical, and relatively high power conversion efficiency (PCE). The PCE of the photovoltaic cells is primarily related to the architecture of the cells, as well as the electrodes and electrolyte employed. Using zinc oxide (ZnO) coupled with two‐dimensional graphene as photoelectrode enables efficient charge transfer and minimizes electron–hole recombination in the DSSCs, resulting in improved performance. This review outlines the feasibility and performance enhancement of ZnO/graphene nanocomposite and its derivatives as photoelectrode for DSSCs. The structural features, optical properties, electron transport, and dye interaction of the ZnO/graphene nanocomposite‐based photoelectrode were considered in this review. In addition, the limitations of ZnO/graphene derivatives as photoelectrodes and their solutions were extensively discussed, as well as their prospects. The ZnO/graphene‐based photovoltaic cells exhibit an efficiency of up to 11.5% under different dyes and electrolytes. The recent progress achieved with this photoelectrode, which is a viable substitute for titanium dioxide (TiO2 ), is also thoroughly reviewed. Abstract : Highlighted the structural, optical, electron transport, limitations, and interaction of dye in ZnO/graphene derivatives for DSSCs. ZnO/graphene‐based DSSCs would be very helpful for researchers studying these materials as photoanode in DSSCs. A detailed electron transport mechanism of ZnO/graphene‐based DSSCs have been intensively reviewed.